Reaction sintering of alumina/mullite nanocomposites from nano-sized starting powders - A. Limpichaipanit (2018)
© 2016 Institute of Materials, Minerals and Mining. Alumina/mullite ceramic nanocomposites were prepared by the mixtures of nano-sized starting powders of alumina with silica and alumina with silicon carbide. Silica from deliberate addition and as the product of silicon carbide oxidation reacted completely with alumina to form mullite. Silica from direct addition segregated at the grain boundary and intergranular mullite was formed whereas silica from oxidation was surrounded by alumina matrix and intragranular mullite was formed after reaction sintering. The most significant difference was fracture behaviour where intragranular mullite nanoparticles promoted transgranular fracture in alumina matrix due to thermal mismatch around nanoparticles and intergranular mullite nanoparticles gave rise to intergranular fracture similar to pure alumina. Wear resistance of the nanocomposites was better than that of alumina. Pull-out formation in the nanocomposites was less and pull-out size was also smaller. Fracture toughness of the nanocomposites was significantly higher than that of alumina.